2013
DOI: 10.1002/mop.27860
|View full text |Cite
|
Sign up to set email alerts
|

A Compact ACS‐FED Dual‐Band Meandered Monopole Antenna for Wlan and WiMax Applications

Abstract: In this article, we present the design of a dual-band (3.5 and 5.8 GHz), meandered monopole antenna for Wireless Local Area Network (WLAN)/Worldwide Interoperability for Microwave Access (WiMAX) applications, which is fed by an asymmetric coplanar strip (ACS). The proposed antenna is comprised of an asymmetric ground plane, an ACS-fed structure, and coupled meandered monopole-type of radiating elements that are designed to provide the two desired operation bands, namely 3.5 and 5.8 GHz. The two resonance frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Various CPW-fed antennas have been reported in literature such as multiband [3][4][5][6][7][8], CPW antennas with added strip for WLAN [9][10][11], and asymmetric coplanar strip antennas [12][13][14][15][16][17][18][19][20]. However, majority of these designs have large antenna dimensions and do not cover all the major bands of WLAN/WiMAX/LTE [13][14][15][16]18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various CPW-fed antennas have been reported in literature such as multiband [3][4][5][6][7][8], CPW antennas with added strip for WLAN [9][10][11], and asymmetric coplanar strip antennas [12][13][14][15][16][17][18][19][20]. However, majority of these designs have large antenna dimensions and do not cover all the major bands of WLAN/WiMAX/LTE [13][14][15][16]18].…”
Section: Introductionmentioning
confidence: 99%
“…However, majority of these designs have large antenna dimensions and do not cover all the major bands of WLAN/WiMAX/LTE [13][14][15][16]18]. Dual-band antenna in [21] with an average gain of 2.5 dB having dimensions 25 mm × 25 mm being compact in size operates only in WLAN band.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the proposed ACS-fed dual-band antenna is compact in size and it is covering all 2.4/5.2/5.8 GHz WLAN and 3.5/5.5 GHz WiMAX frequency bands with acceptable peak gain of 2.8 dBi. Recently some other structures of compact ACS-fed antennas have been reported in [24][25][26][27]. In [24,25] a dualband acs-fed antenna is proposed for 2.4/5.8 GHz WLAN applications by using the concept of loaded capacitance terminations.…”
Section: Introductionmentioning
confidence: 99%
“…To decrease the overall size of the antenna, some designs have been reported in [19][20][21][22][23][24][25][26][27] by using the concept of asymmetric coplanar strip (ACS)-fed. In comparison to general coplanar waveguide (CPW)-fed antenna, an ACS-fed antenna structure will consume only 50% area by considering only half of the ground plane of CPW-fed structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation